Forced convective heat transfer and thermal efficiency assessment in square channel equipped with 10° wavy thin rib - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2020)
Forced convective heat transfer and thermo-hydraulic efficiency in the heat exchanger square channel (HESC) inserted with 10° wavy thin rib (WTR) are reported numerically. The effects of rib height, pitch distance and flow velocity on flow and heat transfer profiles are considered. The rib height to the channel height; e/H or HR, is varied in the range 0.05–0.30, while the rib pitch to the channel height; P/H or PR, is varied in the range 0.50–1.25. The air velocity in the HESC inserted with the WTR is considered in terms of Reynolds number. The Reynolds numbers (Re = 100–2000) for the present investigation is analyzed at the inlet condition. The finite volume method (commercial code) with SIMPLE algorithm is picked to solve the present problem. The numerical model of the HESC inserted with the WTR is validated for both grid independence and verification of the smooth HESC. The numerical results of the HESC inserted with the WTR are printed in terms of flow and heat transfer profiles. The values of Nusselt number, friction factor and thermal efficiency factor in the HESC inserted with the WTR are also plotted. As the numerical result, it is found that the WTR in the HESC can produce the vortex flow that the reason for the enhancements of heat transfer and efficiency. The increment of the heat transfer ability in the HESC is detected when increasing rib height and Reynolds number. In addition, the greatest thermal efficiency factor in the HESC inserted with the WTR is around 3.43 at HR = 0.20, PR = 1, and Re = 2000.
Keywords: heat exchanger; heat transfer; numerical study; thermal efficiency; Wavy thin rib